2011
DOI: 10.1177/0149206311423823
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Alternative Forms of Workplace Voice

Abstract: Workplace voice has been the subject of much research over the past 30 years. Prior work has examined the precursors of a wide variety of voice types including prosocial voice, grievance filing, whistle-blowing, informal complaints, and participation in suggestion systems. However, research on each type of voice has largely been conducted in isolation from work examining alternate types of workplace voice. The goal of this article is to review and integrate the literature on the determinants of workplace voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
252
3
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(278 citation statements)
references
References 128 publications
9
252
3
14
Order By: Relevance
“…One explanation might be that the provision of ideas for improvement, i.e., voice behaviors, does not demand self-initiation from employees to the same extent as other proactive behaviors because employees are directly asked for their opinion. Although this operationalization is in line with current conceptualizations of voice, which likewise include passive forms of employees' voice (Van Dyne et al 2003), the fact, that the provision of ideas for improvement was eased in terms of directly asking for anonymous input might have facilitated voice (Klaas et al 2012). Therefore, additionally reinforcing factors, i.e., organizational pride due to employees' efforts, played a minor role.…”
Section: Limitations and Future Researchsupporting
confidence: 61%
See 1 more Smart Citation
“…One explanation might be that the provision of ideas for improvement, i.e., voice behaviors, does not demand self-initiation from employees to the same extent as other proactive behaviors because employees are directly asked for their opinion. Although this operationalization is in line with current conceptualizations of voice, which likewise include passive forms of employees' voice (Van Dyne et al 2003), the fact, that the provision of ideas for improvement was eased in terms of directly asking for anonymous input might have facilitated voice (Klaas et al 2012). Therefore, additionally reinforcing factors, i.e., organizational pride due to employees' efforts, played a minor role.…”
Section: Limitations and Future Researchsupporting
confidence: 61%
“…Responses were provided on five-point Likert-scales. Second, because the survey was an official employee survey providing feedback to the university's management board, it additionally allowed us to take a behavioral measure of proactivity, i.e., employees' voice in taking part in an organizational suggestion system (Klaas et al 2012). Within the survey, employees were asked to indicate ideas for improving proactive behaviors within the organization in an open question format.…”
Section: Proactive Behaviorsmentioning
confidence: 99%
“…In general, we believe that social network users are likely to engage in voice when one perceives its costs to be low and efficacy to be high. We also expect that, consistent with the findings from the organizational context, in the context of social networks, voice will be the most frequent response to a psychological contract violation, particularly when one intends to restore the relationship (Klaas, Olson-Buchanan, & Ward, 2011). We expect that feelings of anger and betrayal triggered by the perceptions of privacy and/or intellectual property rights breach will motivate Facebook users to speak out, particularly given the platform's social nature.…”
Section: Behavioral Outcomes Associated With Psychological Contract Vsupporting
confidence: 59%
“…134 In health care, the situation is more ambiguous: Klaas et al 135 considered the impact of formal whistleblowing policies and processes within organisations, and reported that such formal instruments were likely to make whistleblowing appear to be a strategy of last resort, as it could be perceived as an open challenge to the authority of management. However, the existence of clear professional standards and guidelines has been found to be an important factor in supporting whistleblowing in health care in a number of empirical studies 86,95,101,102,136 and particularly in nursing rather than other health-care professions.…”
Section: Professional Standards Including Ethical Codes Of Practice mentioning
confidence: 99%